Elucidating the Potential Mechanism of Ulcerative Colitis Amelioration by Artemisia annua L. Based on Network Pharmacology and Experimental Validation - Shen, Yujie; Li, Luxiu; Hu, Xin; Yang, Ming; Chen, Wei; Xu, Guoqiang (Combinatorial Chemistry & High Throughput Screening, 2025)
<span class=
Keywords: network pharmacology